Treatment and reuse of gray water using a slow sand filter - Madueño Valdez, Leonardo (2018)
We find ourselves with a deficient use of drinking water, either due to waste or misuse. In the present project, the main problem found in the educational center was the use of potable water for the irrigation of the green garden and other green areas, for which the following alternative was implemented, which consists in the reuse of gray water obtained from the running laundries located outside the sanitary services through the implementation of a system which consists of a catchment, storage and sedimentation tank, filtration tank, storage tank for its later distribution for irrigation. The types of irrigation implemented are of the drip type and by gravity. The results obtained in this project were as expected, since irrigation was achieved efficiently with water that presents a lower degree of contamination when leaving the filtration tank.